Dino-mummy - Sperring, Mark; Lloyd, Sam (London : Bloomsbury, 2014)
It's not easy being a Dino-Mummy, especially when you have two roaring little dinos to take care of. But somehow Dino- Mummy makes everything look so easy. Do you know a secret? I'm sure you dino-do! It's something rather special about a certain 'you know who'! From the moment that you wake up, she's a sing-song superstar, Singing out Good morning! with a dino Tra la la! Dino-Mummy is AMAZING, and whether it's morning, noon or night, she's always on hand. After all, life in the dino family is just as fun (and chaotic) as ever.
Keywords: Children's stories